Exploring oral communication anxiety among translators at the Saif Bin Zayed Academy: case study of newly recruited translator - Mussa, Ibtihal Hassan; Alhasan, Rashad F; Alwreikat, Emad A; Alqaryouti, Marwan Harb (Research Journal in Advanced Humanities, 2026)
This qualitative study investigates the psychological processes and mechanisms of Oral Communication Apprehension (OCA) in English used by translators at the Saif Bin Zayed Academy for Police and Security Sciences (SBZA) in the UAE. A purposive sample of five translators working in different departments at SBZA, where English is an important medium of communication, was selected. Interviews were held to understand their apprehensive actions in oral communication situations. The results showed that the apprehensive actions were a result of fear of negative evaluation, avoidance of professional engagement, speaking anxiety, lack of confidence in English proficiency, and self-criticism. Strategies to overcome these psychological hurdles to ensure smooth communication and increased speaking fluency in professional settings are proposed.